Investigation methods on continental outcrops: developing an upgrade of the architectural analysis method by field tests in well-exposed Sardinian outcrops - Costamagna, Luca Giacomo (Journal of Mediterranean Earth Sciences, 2018)
In order to perfect the analytical procedures used to investigate the continental depositional environments, an upgrade of the architectural analysis method is here proposed in its main lines. The method has been tested in several well-exposed outcrops pertaining to continental environments related to different units of various age outcropping in different parts of Sardinia. The method appears to be promising in determining the fluvial style and the features of the corresponding fluvial network of the investigated units throughout a careful analysis of a discrete number of well-exposed outcrops.